PENGARUH METODE BERCERITA MELALUI VIDEO ANIMASI UNTUK MENINGKATKAN KEMAMPUAN BERBICARA PADA ANAK KELOMPOK B DI TK SAVE THE KIDS BANDA ACEH - Amini Rahmah; Riza Oktariana; Raudha Meutia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low speaking ability of Group B children at TK Save The Kids Banda Aceh, which is indicated by a lack of confidence in speaking, limited vocabulary, and difficulty in forming simple sentences. This study aims to determine the effect of the storytelling method through animated videos on improving children's speaking skills. This research uses a quantitative approach with a quasi-experimental design, specifically a one-group pre-test and post-test design. The subjects of this study consisted of 20 children aged 5–6 years. Data collection techniques were carried out through observation using a speaking ability assessment rubric that includes indicators such as confidence, fluency, clarity of pronunciation, and the ability to construct simple sentences. The research procedure includes a pre-test to determine the children's initial speaking ability, followed by treatment in the form of storytelling activities using animated videos, and a post-test to measure improvement after the treatment. The results of the study show a significant improvement between the pre-test and post-test scores, where the children's speaking ability, which was initially in the categories of not yet developed and beginning to develop, increased to developing as expected and very well developed. The use of animated videos has proven to attract children's attention, increase learning motivation, and help them understand storylines while enriching their vocabulary. Therefore, it can be concluded that the storytelling method through animated videos has a positive effect on improving the speaking ability of Group B children at TK Save The Kids Banda Aceh